IFN-γ action in the media of the great elastic arteries, a novel immunoprivileged site - Dal Canto, Albert J. (American Society for Clinical Investigation, 2001)
Infection of medial smooth muscle cells with γ-herpesvirus 68 (γHV68) causes severe chronic vasculitis that is restricted to the great elastic arteries. We show here that persistence of disease in the great elastic arteries is (a) due to inefficient clearance of viral infection from this site compared with other organs or other vascular sites, and (b) associated with failure of T cells and macrophages to enter the virus-infected elastic media. These findings demonstrate immunoprivilege of the media of the great elastic arteries. We found that IFN-γ acted on somatic cells during acute infection to prevent the establishment of medial infection and on hematopoietic cells to determine the severity of disease in this site. The immunoprivileged elastic media may provide a site for persistence of pathogens or self antigens leading to chronic vascular disease, a process regulated by IFN-γ actions on both somatic and hematopoietic cells. These concepts have significant implications for understanding immune responses contributing to or controlling chronic inflammatory diseases of the great vessels.